Expressions of IL4, IL10, and IFNγ cytokines genes during bacterial mastitis (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Many bacteria are involved in causing mastitis in dairy cows. Perfect identification of bacteria is crucial for the appropriate choice of drug for treatment. This study aims to find out the various bacteria that cause mastitis through the 16S ribosomal ribonucleic acid (16S rRNA) gene. Materials and Methods: A total of 150 mastitis somatic cell samples were tested with bacterial nested polymerase chain reaction (PCR) universal primers, targeting the 16S rRNA gene. The primers had both Gram-positive and Gram-negative bacterial specificities. Inflammatory cytokine interleukin (IL-10), IL-4, and interferon-gamma (IFNγ) expression genes were measured and compared in mastitis-free and mastitis-affected animals. Results: Based on the PCR, 70 (46.7%) samples showed positive results. The expression of the IL-10 gene was significantly higher (p < 0.001) in mastitis-affected cows than noninfected animals. Compared to cows diagnosed with clinical mastitis, the IL-4 and IFNγ genes were expressed more strongly in healthy cows (p < 0.0001). Conclusion: Mastitis has been linked to both Gram-positive and Gram-negative bacteria. These genes are strong predictors of mastitis in the states analyzed, as evidenced by the differential expression in mastitis and healthy conditions of the IL-4, IL-10, and IFNγ genes. The genes examined here and others will be the subject of additional research J. Adv. Vet. Anim. Res., 9(1): 42–52, March 2022http://doi.org/10.5455/javar.2022.i567